2011
DOI: 10.1177/105268461102100106
|View full text |Cite
|
Sign up to set email alerts
|

What Leadership Looks Like: Using Photography to See the School Leaders that City Youth Desire

Abstract: In the city setting in which this article's investigation took place, high school dropout rates have remained above 50% for better than three decades. This article reports on a photographic inquiry into urban youth's perceptions of the very institution of school, revealing reasons behind the multigenerational school disengagement represented by these graduation rate statistics. Relying on visually based mechanisms with which city students are already proficient, the findings suggest that these tools can provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…Using photos in the interview process also promotes deeper reflection on the part of the participants (Clark, 1999;Zenkov, Harmon, Bell, Ewaida & Lynch, 2011). Interviews are often conducted weeks or months after photos are taken.…”
Section: Benefits and Obstaclesmentioning
confidence: 99%
See 1 more Smart Citation
“…Using photos in the interview process also promotes deeper reflection on the part of the participants (Clark, 1999;Zenkov, Harmon, Bell, Ewaida & Lynch, 2011). Interviews are often conducted weeks or months after photos are taken.…”
Section: Benefits and Obstaclesmentioning
confidence: 99%
“…As a research tool, PEI is an especially powerful method for understanding school context through the eyes of students (Lutrell, 2010;Meo, 2010;Zenkov et al, 2011). In school research, children are the clients around which most policy decisions are made; however, researchers frequently leave children out of any discussion of the ways in which policies impact them or might best serve them.…”
Section: Implications For Research Policy and Practicementioning
confidence: 99%
“…When elders expect youth to become politically engaged, youth may very well begin to take on the role of political actors in their communities (Ginwright, 2010). At times, these encounters with the politically engaged can be discouraging but they may also contribute to building trust (Zenkov, Harmon, Bell, Ewaida, & Lynch, 2011) and widening youths' circle of support.…”
Section: Encourage Youth To Interact With Community Activistsmentioning
confidence: 99%
“…According to Hogan and Kaiser (2005), youth "leadership is one of the most important topics in the human sciences and historically one of the more poorly understood" (p. 169). Research has been conducted quantitatively (Antonakis, Avolio, & Sivasubramaniam, 2003;Chan & Drasgow, 2001;Guerin et al, 2011;Oakland, Falkenberg, & Oakland, 1996;Ogurlu & Emir, 2013;Schneider, Ehrhart, & Ehrhart, 1999;Zacharatos, Barling, & Kelloway, 2002) and qualitatively (Close & Lechman, 1997;Ferguson, Kim, & McCoy, 2011;Haber, 2011;Hammond-Diedrich & Walsh, 2006;Hastings, Barrett, Barbuto, & Bell, 2011;Komives, Mainella, Longerbeam, Osteen, & Owen, 2006;Mortensen et al, 2014;Mullen & Tuten, 2004;Roach et al, 1999;Webster & Worrell, 2008;Zenkov, Harmon, Bell, Ewaida, & Lynch., 2011). These diverse explorations on youth leadership and its development revealed that adolescent leaders are motivated, socially and culturally competent, self-directed, responsible, compassionate, and community-oriented.…”
Section: Further Research Needed On Youth Leadershipmentioning
confidence: 99%